A case of relapsed Mycobacterium chelonae pulmonary infection presenting with severe weight loss and treated with a combination of antibiotic therapy and percutaneous feeding. (February 2021) - Pease, C.; Alvarez, G.G.
Abstract: Mycobacterium chelonae is a type of nontuberculous mycobacteria most commonly associated with skin and soft tissue infections. We present a case of recurrent M. chelonae pulmonary infection presenting with severe weight loss. After recurrence, sputum cultures remained positive for 2 years despite appropriate antibiotics. Cultures only became negative after the addition of intravenous imipenem and jejunostomy feeds. The rarity of M. chelonae pulmonary infection means that optimal treatment regimens have not yet been fully established but a regimen of clarithromycin plus an additional antibiotic has been recommended 1 . The prognosis of such infections also remains unclear but lower rates of macrolide resistance suggest that the prognosis may be better than the closely related species M. abscessus . Although its benefit has not been proven, nutrition supplementation, including percutaneous enteral feeding, can be considered for refractory NTM infection in underweight patients.